The Use of "Time Board" Learning Media in Mathematics Learning Theme 8 Grade II Elementary School Griya Bandung Indah - Dinie Anggraeni Dewi; Hasna Salsabila; Rieke Siti Sarah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Currently students do not like mathematics. This phenomenon occurs due to the unavailability of interesting learning media for them. Not a few teachers who rely on books only. This study intends to see how the use of timeboard learning media in learning mathematics theme 8 class II SDN Griya Bandung Indah. The results obtained showed that the activeness of students during the learning process reached 91.95%, which means that the active category was fulfilled. The results of the student response questionnaire reached 89%, which means that the positive category was fulfilled. So the use of time board learning media in learning mathematics theme 8 class II SDN Griya Bandung Indah is said to be effective.